- #1

Sciencer

- 8

- 0

In the equation

y(x,t) = ym * sin(kx - wt - PHI)

I thought I understand why we have that phase constant atleast mathmetically but after thinking about it I don't think I understand it completely like here in my book it says the phase constant moves the wave forward or backward in space or time. Now let's say

we have wave at t = 0 and x = 0;

we would have y(x,t) = ym * sin(-PHI) that wouldn't really move it forward or backward in space or time if we had y(x,t) = ym + PHI then yeh it would have but I don't see how it would moves it backward or forward in that case ?

I can see how they derived

y(x,t) = ym * sin(kx - wt) but that PHI keeps confusing me.